2009
DOI: 10.1007/s00213-009-1706-1
|View full text |Cite
|
Sign up to set email alerts
|

A 22-week, multicenter, randomized, double-blind controlled trial of Crocus sativus in the treatment of mild-to-moderate Alzheimer’s disease

Abstract: This phase II study provides preliminary evidence of a possible therapeutic effect of saffron extract in the treatment of patients with mild-to-moderate Alzheimer's disease. This trial is registered with the Iranian Clinical Trials Registry (IRCT138711051556N1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(138 citation statements)
references
References 33 publications
(44 reference statements)
5
128
1
2
Order By: Relevance
“…Scientific studies have confirmed the validity of saffron extracts in the treatment of mild to moderate depression [5,6], and agent against erectile dysfunction [7], and as anti-arrhythmic agent and restorer of cardicac functions [8,9]. Other studies showed a role of saffron as a protector against age related macular degeneration [10,11], in reducing cognitive decline in patients with Alzheimer Disease [12,13], and as a source for potential anti-cancer agents [14,15,16].…”
Section: Introductionmentioning
confidence: 93%
“…Scientific studies have confirmed the validity of saffron extracts in the treatment of mild to moderate depression [5,6], and agent against erectile dysfunction [7], and as anti-arrhythmic agent and restorer of cardicac functions [8,9]. Other studies showed a role of saffron as a protector against age related macular degeneration [10,11], in reducing cognitive decline in patients with Alzheimer Disease [12,13], and as a source for potential anti-cancer agents [14,15,16].…”
Section: Introductionmentioning
confidence: 93%
“…It is now clear that saffron water or alcohol extracts may have anti-anxiety (Pitsikas et al, 2008;Hosseinzadeh & Noraei, 2009) and antidepressant effects (Akhondzadeh et al, 2004;Moshiri et al, 2006;Akhondzadeh Basti et al, 2007). Moreover, the extract can improve the signs of Alzheimer's disease (Akhondzadeh et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…It is an interesting finding showing that saffron extract may be a useful tool for reduction of both metabolic and behavioral stress side effects. The effects of saffron extract on several functions of CNS including learning and memory improvement (Pitsikas & Sakellaridis, 2006;Pitsikas et al, 2007), reduction of anxiety signs (Pitsikas et al, 2008;Hosseinzadeh & Noraei, 2009), improvement of depression (Rios et al, 1996;Schmidt et al, 2007), and Alzheimer's disease (Akhondzadeh et al, 2010) have been indicated in previous studies in human and animal models. In addition, data exist showed that saffron extract can inhibit sigma opioid and NMDA glutamate receptors in vivo (Lechtenberg et al, 2008).…”
Section: Behavior Groupsmentioning
confidence: 99%
“…Onset of tremor increased with the extracts (80 and 160 mg/kg) in prophylactic study, as the effect observed with propranolol at the dose of 5 mg/kg. Safranal did not affect the latency of tremor [111]. The effects of aqueous and ethanolic extracts of Crocus sativus stigma and its constituents were evaluated on morphine-withdrawal syndrome in mice.…”
Section: Stmentioning
confidence: 98%